Desarrollo de un biorreactor de bajo costo para la disminución de los requerimientos de oxígeno externo en un consorcio alga-bacteria para la producción de Polihidroxialcanoatos (PHA) (2020)
Developed a fully functional, low-cost bioreactor capable of maintain a controlled, aseptic and biologically active environment. This achieved, through the conceptual design of the equipment; defining the characteristics process to establish the selection criteria (volume, material, operating mode, agitation system, geometry, operating chamber incubation and optical measuring sensor), which were used to bibliographical references and experimentation. After the design, the construction of different prototypes was carried out, which were subjected to different tests in order to evaluate their functioning and viability. In addition, the selected prototype has a device capable of continuously and automatically monitoring cell growth in real time using an optical sensor; based on its simplicity and flexibility, it allows modeling microbial growth curves. Its cost equivalent to the current year (2020) is $1’627,300(COP) with an equivalent of $481.09(US).